Comparison of intraductal ultrasonography findings between primary sclerosing cholangitis and IgG4‐related sclerosing cholangitis. Issue 6 (June 2015) - Naitoh, Itaru; Nakazawa, Takahiro; Hayashi, Kazuki; Miyabe, Katsuyuki; Shimizu, Shuya; Kondo, Hiromu; Nishi, Yuji; Yoshida, Michihiro; Umemura, Shuichiro; Hori, Yasuki; Kato, Akihisa; Okumura, Fumihiro; et al.
Abstract Background and Aim Comparisons of intraductal ultrasonography (IDUS) findings between primary sclerosing cholangitis (PSC) and IgG4‐related sclerosing cholangitis (IgG4‐SC) have not been elucidated. We aimed to clarify the differences in transpapillary IDUS findings between PSC and IgG4‐SC. Methods We retrospectively compared transpapillary IDUS findings between 15 patients with PSC and 35 patients with IgG4‐SC between 2004 and 2014. Results IDUS findings of circular‐asymmetric wall thickness, irregular inner margin, diverticulum‐like outpouching, unclear outer margin, heterogeneous internal echo, and disappearance of three layers were significantly higher in PSC than in IgG4‐SC (P < 0.001). Irregular inner margin, diverticulum‐like outpouching, and disappearance of three layers were specific IDUS findings for PSC compared to IgG4‐SC. Diverticulum‐like outpouching on IDUS and endoscopic retrograde cholangiogram (ERC) was observed in 10 (67%) and five (33%) of 15 patients with PSC, respectively. However, based on IDUS and ERC, diverticulum‐like outpouching was not observed in any patient with IgG4‐SC. All five patients with diverticulum‐like outpouching on ERC had diverticulum‐like outpouching on IDUS, and five (50%) of 10 patients without diverticulum‐like outpouching on ERC had diverticulum‐like outpouching on IDUS. Conclusions The IDUS findings differed between PSC and IgG4‐SC. Irregular inner margin, diverticulum‐like outpouching, and disappearance of three layers are specific IDUS findings for PSC compared to IgG4‐SC. IDUS is a more useful procedure than ERC for the early detection of diverticulum‐like outpouching.